2005
DOI: 10.2337/diacare.28.9.2206
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Efficacy of Methods Used in Screening for Lower-Limb Arterial Disease in Diabetes

Abstract: OBJECTIVE -Foot-related disease is the most common cause for hospital admission among the diabetic population. Lower-limb peripheral arterial occlusive disease (PAOD) is a major risk factor in diabetic foot disease. Screening for PAOD commonly includes foot pulses and the ankle-brachial pressure index (ABPI) and/or the toe-brachial pressure index (TBI), but concerns persist regarding their accuracy. We evaluated the efficacy of several commonly used screening methods in different subject populations.RESEARCH D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
298
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(320 citation statements)
references
References 16 publications
12
298
0
10
Order By: Relevance
“…The results in the non-diabetic control group were almost similar (sensitivity 83% and specificity 100%). 12 Alnaeb et al reported a correlation of −0.81 between an ABI <0.9 and arterial DUS in the same type of diabetic patients.…”
Section: -7mentioning
confidence: 99%
“…The results in the non-diabetic control group were almost similar (sensitivity 83% and specificity 100%). 12 Alnaeb et al reported a correlation of −0.81 between an ABI <0.9 and arterial DUS in the same type of diabetic patients.…”
Section: -7mentioning
confidence: 99%
“…The prevalence of diabetes in the group with an ABI > 1.4 was 58%, compared with 18% and 48% in those with a normal ABI or those with an ABI < 0.9 [37] . It has long been known that the sensitivity of the ABI to correctly diagnose PAD is considerably reduced in the presence of arterial media calcification and that, clinically, this calcification is associated with the presence of peripheral neuropathy [38,39] . Accordingly, in the presence of peripheral neuropathy it is recommended to use an alternative method, such as flow wave analysis using Doppler colour ultrasound [40,41] .…”
Section: Diagnosis Of Pad In Diabetesmentioning
confidence: 99%
“…[72] Certainly its use in patients with diabetes mellitus has been criticized because arterial medial calcification may cause spuriously elevated ankle pressures, even more so in patients with ESRD. [70,71,73,74] This potential underestimation of peripheral arterial disease may be circumvented by measuring toe pressures, but such measurement requires more sophisticated equipment and trained personnel. [70,71,73,74] Transcutaneous oxygen pressure (TcPO 2 ), Duplex imaging, and angiography represent further modalities used in a more comprehensive evaluation of peripheral circulation, especially prior to revascularization.…”
Section: The Diabetic Foot In Renal Failure: Examination and Risk Estmentioning
confidence: 99%
“…[70,71,73,74] This potential underestimation of peripheral arterial disease may be circumvented by measuring toe pressures, but such measurement requires more sophisticated equipment and trained personnel. [70,71,73,74] Transcutaneous oxygen pressure (TcPO 2 ), Duplex imaging, and angiography represent further modalities used in a more comprehensive evaluation of peripheral circulation, especially prior to revascularization. [33,70,71] Diabetic neuropathy is also diagnosed clinically.…”
Section: The Diabetic Foot In Renal Failure: Examination and Risk Estmentioning
confidence: 99%